Comparative grain storage analysis - Wagner, Christopher (Kansas State University, 2013)
Grain Elevators have towered the plains of Southwest Kansas for over the last half of a century. Many of these large white concrete structures were built during the 1950s using a slip form concrete design. While new grain storage has been built over time, many of the original slip form structures remain a large part of the farm cooperatives storage capacity. Grain production has continued to increase and put greater demand on storage facilities and handling capabilities. Thus, there is a need for cooperatives to meet the future demands of farmers by replacing or updating grain storage assets. The objective of this project is to provide a comparative analysis of grain storage options that a cooperative, primarily the Garden City Co-op, Inc. (GCC), could utilize in making a decision to update or replace grain storage assets. The project examines three different options for grain storage including concrete, steel, and bunker storage. The project will also examine extending the life of an original slip form elevator by installing a gunite bin liner. To determine which option that provides the most economic benefit to GCC and its members, Net Present Value and the Internal Rate of Return are estimated for each grain storage option. GCC historical grain handling margins and grain storage costs were derived from historical averages and bids from projects GCC has undertaken in the past five years, respectively. The model assumes receipts as a percentage of storage to accurately represent bushels handled by a facility. Grain storage is highly variable in initial cost and the operational needs will change in every circumstance. The results indicate that a large volume of grain is needed before economic profits will be realized.
Keywords: Cooperative; Grain elevator; Net present value